Strategi Pengembangan SDM LAZ PERSADA Cabang Pamekasan dalam Menghadapi Tantangan Digitalisasi Era Society 5.0 - Velayati, Ayatullah Vava; Badriyah, Nurul; Rahmawati, Mardiana; Bariyah, Choiril; Haryanto, Rudy (Faculty of Islamic Economics and Business, Madura Islamic State University, 2024)
Abstract: The Era of Society 5.0 is an era where information and communication technology has been integrated with human life in all aspects. This era is marked by the emergence of artificial intelligence, Internet of Things, robotics, and other technologies that enable humans to live more easily, comfortably, and efficiently. Human resources in the era of society 5.0 are expected to be more professional and qualified and fully competent in all areas of life, which is expected to include the company's HR performance. One of the institutions that requires human resource development to face the challenges of the society 5.0 era is LAZ PERSADA, Pamekasan branch. The research aims to analyze the HR Development Strategy of LAZ PERSADA Pamekasan Branch in Facing the Challenges of Digitalization in the Age of Society 5.0. The research method used is qualitative with the type of field research. Based on the analysis, there are several strategies that LAZ PERSADA Pamekasan Branch can use to improve the institution to become better, namely by (1) training in the field of zakat management and distribution. (2) synergy between the head office and branches to conduct evaluations, coaching and training every now and then for LAZ PERSADA Pamekasan branch employees. And (3) serious training in the field of digitalization of technology, especially in the Artificial Intelligence section in facing the challenges of digitalization in the era of society 5.0. Keywords: Society 5.0, HR Development, Digitalization Abstrak: Era Society 5.0 merupakan era dimana teknologi informasi dan komunikasi telah terintegrasi dengan kehidupan manusia dalam semua aspek. Era ini ditandai dengan munculnya Artificial Intelligence, Internet of Things, robotika, dan teknologi lainnya yang memungkinkan manusia untuk hidup lebih mudah, nyaman, dan efisien. Sumber daya manusia era society 5.0 diharapkan lebih profesional serta berkualitas juga berkompeten penuh di semua bidang kehidupan, harapannya termasuk dalam kinerja SDM perusahaan. Salah satu lembaga yang memerlukan pengembangan SDM dalam menghadapi tantangan era society 5.0 yakni LAZ PERSADA cabang Pamekasan. Penelitian bertujuan untuk menganalisis Strategi Pengembangan SDM LAZ PERSADA Cabang Pamekasan dalam Menghadapi Tantangan Digitalisasi Era Society 5. Metode Penelitian yang digunakan adalah Kualitatif dengan jenis penelitian studi lapangan (field research). Berdasarkan analisa terdapat beberapa strategi yang bisa digunakan LAZ PERSADA Cabang Pamekasan dalam menyempurnakan lembaga untuk menjadi lebih baik yaitu dengan cara (1) pelatihan pada bidang pengelolaan dan pendistribusian zakat.(2) sinergitas antara kantor pusat dan cabang untuk mengadakan evaluasi, pembinaan dan pelatihan setiap beberapa waktu terhadap karyawan LAZ PERSADA cabang Pamekasan. Dan (3) pelatihan yang serius di bidang digitalisasi teknologi utamanya pada bagian Artificial Intelligence dalam menghadapi tantangan digitalisasi pada era society 5.0. Kata Kunci: Masyarakat 5.0, Pengembangan SDM, Digitalisasi